Role Perception of Occupational Therapists in Education Systems: Self-Efficacy and Employability Skills - Yael Fogel; Liron Lamash (Occupational Therapy International)
Although the main framework for occupational therapy includes delivery of services in educational institutions with students with disabilities, little is known about how the occupational therapists perceive their role in this specific system. This research examines an integrated conceptual model wherein self-efficacy explains the occupational therapists’ role perception with employability skills as a mediator. Participants, 147 occupational therapists working in educational systems, completed an online demographic questionnaire, the Perception Questionnaire for Occupational Therapists in the Education System, General Self-Efficacy Questionnaire, and Employability Key Questionnaire. The proposed model was analyzed by the structural equation model (SEM) using AMOS software. The SEM provided excellent goodness of fit indices, χ224=40.49; p=.019; NFI=.93; CFI=.97; RMSEA=.07; SRMR=.05, and explained 40% of the variance in role perception. These findings highlight employability skills as the primary contributor that affects occupational therapists’ role perception. Self-efficacy and employment skills influence how occupational therapists working in education systems perceive their roles; thus, employment skills should be included in professional training and development courses. This study has implications for occupational therapists working on the education system to understand the meaningful effects of employability skills as critical to developing and improving their role perception.